2017
DOI: 10.21873/anticanres.11755
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Reactivation in a Patient Receiving Chemotherapy for Breast Cancer: A Case Report

Abstract: Hepatitis B virus (HBV) reactivation is a known complication of immunosuppressive therapy. While patients who are undergoing treatment with anti-CD20 agents or stem cell transplantation are commonly screened for chronic HBV infection prior to treatment, there are no consensus guidelines regarding HBV screening for patients undergoing chemotherapy for solid tumors. We present a rare case of fulminant liver failure due to HBV reactivation in a patient receiving chemotherapy for breast cancer. Our case highlights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“… 23 A case report documented PTX-induced HBV reactivation in a breast cancer patient who eventually died due to severe liver and kidney failure. 11 However, there is no clear consensus on whether HBV reactivation occurs as a result of the underlying disease itself, the PTX treatment, or the interaction between the two factors. 4 In the present study, PTX was found to directly promote HBV replication in vitro in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 A case report documented PTX-induced HBV reactivation in a breast cancer patient who eventually died due to severe liver and kidney failure. 11 However, there is no clear consensus on whether HBV reactivation occurs as a result of the underlying disease itself, the PTX treatment, or the interaction between the two factors. 4 In the present study, PTX was found to directly promote HBV replication in vitro in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical trials have reported cases of severe HBV reactivation leading to liver damage in breast cancer patients following PTX treatment. 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation